The Characterization of a Gonococcal HicAB Toxin–Antitoxin System Capable of Causing Bacteriostatic Growth Arrest - Salwa S. Bagabas; Jorge Trujillo-Mendoza; Michael J. Stocks; David P. J. Turner; Neil J. Oldfield (Microorganisms)
Neisseria gonorrhoeae is the causative agent of the sexually transmitted infection gonorrhea. Preventative vaccines or novel treatments based on a better understanding of the molecular basis of N. gonorrhoeae infection are required as resistance to current antibiotics is widespread. Toxin–antitoxin (TA) systems modulate bacterial physiology by interfering with vital cellular processes; type II TA systems, where both toxin and antitoxin are proteins, are the best-studied. Bioinformatics analysis revealed genes encoding an uncharacterized type II HicAB TA system in the N. gonorrhoeae strain FA1090 chromosome, which were also present in >83% of the other gonococcal genome sequences examined. Gonococcal HicA overproduction inhibited bacterial growth in Escherichia coli, an effect that could be counteracted by the co-expression of HicB. Kill/rescue assays showed that this effect was bacteriostatic rather than bactericidal. The site-directed mutagenesis of key histidine and glycine residues (Gly22, His24, His29) abolished HicA-mediated growth arrest. N. gonorrhoeae FA1090∆hicAB and complemented derivatives that expressed IPTG-inducible hicA, hicB, or hicAB, respectively, grew as wild type, except for IPTG-induced FA1090∆hicAB::hicA. RT-PCR demonstrated that hicAB are transcribed in vitro under the culture conditions used. The deletion of hicAB had no effect on biofilm formation. Our study describes the first characterization of a HicAB TA system in N. gonorrhoeae.